Strength training is ineffective for oxidative metabolism - Schantz, P. G.; Kallman, M. (Swimming Technique, 1989)
This study attempted to determine the relationship between strength training program effects and aerobic endurance adaptations. Strength training programs are generally considered to be anaerobic in nature. Implication: It was concluded that strength training does not effect the enzymes associated with aerobic metabolism (some studies say that it does). Consequently, training needs to be specific for the energy system required in the sport. To exceed one's regular training program through extra work, such as dry-land training, may not be harmful, but to decrease training from beneficial sport-specific work by adding auxiliary activities will not help and could even hinder performance development.